CTNI-76. PHASE 2 CLINICAL TRIAL OF VAL-083 IN NEWLY DIAGNOSED MGMT-UNMETHYLATED GBM. (9th November 2020) - Chen, Zhong-ping; Guo, Cheng-Cheng; Yang, Qun-ying; Wu, Shao-xiong; Li, Jia-Wei; Bacha, Jeffrey; Johnson, Greg; Langlands, John; Schwartz, Richard; Kwan, Claire; Kanekal, Sarath; Steino, Anne; et al.
Abstract: Approximately 60% of glioblastoma multiforme (GBM) patients possess an unmethylated methylguanine DNA-methyltransferase (MGMT) promoter region, which confers a limited response to standard-of-care treatment with temozolomide (TMZ), resulting in shorter median survival when compared to patients with methylated MGMT promoter. VAL-083 is a novel bi-functional DNA targeting agent that induces inter-strand cross-links at N 7 -guanine, leading to DNA double-strand breaks and ultimately cell death. VAL-083 circumvents MGMT-mediated TMZ resistance in vitro and in vivo . A Phase 2 study has been initiated for VAL-083 in newly diagnosed MGMT unmethylated GBM. The study has 2 stages: Stage 1 is a dose-escalation safety and tolerability phase to confirm the phase 2 dose of VAL-083 when administered concurrently with radiation therapy (RT). Patients received VAL-083 at 20, 30, or 40 mg/m 2 /day x 3 days every 21 days along with standard radiation treatment (RT) (2 Gy/day, 5 days/week). The dose escalation stage is complete, and 30 mg/m 2 /day of VAL-083 in combination with RT was generally safe and well-tolerated. Stage 2 comprises an expansion phase to enroll up to 20 additional patients at the 30 mg/m 2 /day of VAL-083 in combination with RT. As of June 2, 2020, all patients have been enrolled, with a total of 29 patients in the study, and 25 patients receiving 30 mg/m 2 /day VAL-083. Of the 29 patients enrolled, 27 have completed their prospectively planned MRI scans and had their initial assessment for tumor response. Two additional patients died prior to their post-cycle 3 MRI. Consistent with our prior experience, myelosuppression was the most common adverse event. Three patients have experienced dose-limiting toxicities - one (1/3; 33%) at the 40 mg/m 2 /day and two (2/25; 8%) at the 30 mg/m 2 /day dose. Further safety and efficacy updates will be presented at the meeting. Clinicaltrials.gov identifier: NCT03050736.